Circling around the Really Real: Spirit Possession Ceremonies and the Search for Authenticity in Bahian Candomblé - Port, Mattijs van de (Ethos, 2005)
Many anthropologists studying spirit possession cults have commented that the most immediate experience of possession escapes our understanding. In Bahian candomblé, cultists have reached similar conclusions: while their religious discourse explains why possession happens, the phenomenon itself is considered to be hors discours—“locked-up” in the here and now of the experiencing body. This article discusses how the construction of possession as “radically other” helps the priesthood to deal with the fact that candomblé has become the trademark of the Bahian state, and ever more voices are involved in a debate as to what the cult is, can be or should be. In response, priests have put the inexplicability of possession at the service of authenticating their particular understanding of candomblé. Declaring words to be inadequate to grasp the really real of their religion, they seek to restore their authority.